2017
DOI: 10.1016/j.jid.2017.02.966
|View full text |Cite
|
Sign up to set email alerts
|

Global Associations between UVR Exposure and Current Eczema Prevalence in Children from ISAAC Phase Three

Abstract: We sought to examine the relationship globally between UVR dose exposure and current eczema prevalences. ISAAC Phase Three provided data on eczema prevalence for 13- to 14-year-olds in 214 centers in 87 countries and for 6- to 7-year-olds in 132 centers in 57 countries. Linear and nonlinear associations between (natural log transformed) eczema prevalence and the mean, maximum, minimum, standard deviation, and range of monthly UV dose exposures were assessed using linear mixed-effects regression models. For the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 27 publications
(33 reference statements)
2
7
0
Order By: Relevance
“…28 AD prevalence is inversely associated with sunlight exposure, 29 and the strong correlation between latitude and AD is likely secondary to differences in ultraviolet exposure. 8 Our findings are complementary to these prevalence data; a decrease in 50 h of bright sunlight over the course of a month correlated with an increase of~134 TCI prescriptions. These results parallel the effects of cloud cover on healthcare utilization: a 10% increase in cloud cover correlated with an increase of~9 hospital/clinic monthly visits for AD and ~262 TCI prescriptions.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…28 AD prevalence is inversely associated with sunlight exposure, 29 and the strong correlation between latitude and AD is likely secondary to differences in ultraviolet exposure. 8 Our findings are complementary to these prevalence data; a decrease in 50 h of bright sunlight over the course of a month correlated with an increase of~134 TCI prescriptions. These results parallel the effects of cloud cover on healthcare utilization: a 10% increase in cloud cover correlated with an increase of~9 hospital/clinic monthly visits for AD and ~262 TCI prescriptions.…”
Section: Discussionsupporting
confidence: 69%
“…It has been proposed that decreased environmental ultraviolet light exposure may be an important driver of the global increasing AD prevalence . AD prevalence is inversely associated with sunlight exposure,and the strong correlation between latitude and AD is likely secondary to differences in ultraviolet exposure . Our findings are complementary to these prevalence data; a decrease in 50 h of bright sunlight over the course of a month correlated with an increase of ~134 TCI prescriptions.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…An autumn–winter birth has also been associated with an increase in AD prevalence, and a U.S. study found that AD prevalence was higher in areas with more indoor heating, lower relative humidity, lower mean temperatures, higher precipitation and lower ultraviolet index . Most recently, a worldwide ecological analysis using ISAAC (The International Study of Asthma and Allergies in Childhood) phase III data reported a positive linear association between country‐level AD prevalence and certain metrics of ultraviolet radiation exposure, and nonlinear relationships with other metrics of ultraviolet radiation exposure. These associations were significant among 13–14 year olds, but not in 6–7 year olds.…”
Section: Environmental Factorsmentioning
confidence: 99%
“…An ecological analysis of ISAAC data demonstrated a positive linear correlation between country-level monthly minimum and mean UVR exposure and AD prevalence, particularly among 13-to 14-year-olds. 18 Lower AD prevalence is also associated with areas of high relative humidity, high temperatures and low use of central heating. 19,20 Recent data from Denmark highlight that the inverse of the above weather conditions is conducive to AD flares, using healthcare utilization as a surrogate marker for exacerbations.…”
Section: Ultraviolet Radiation Temperature and Humiditymentioning
confidence: 99%